Political Legitimacy in Crisis: A Weberian Reading of W. B. Yeats’s “The Second Coming" - Akbay, Yakut (Turkey, 2026)
W. B. Yeats’s “The Second Coming” (1919) has long been regarded as a prophetic reflection on political and social unrest. This article examines Yeats’s poem within the framework of Max Weber’s theory of political authority. Weber categorises legitimacy into three forms: traditional, legal-rational, and charismatic. Yeats’s evocative image, “Things are falling apart; the centre cannot hold”, conveys the fragmentation of both traditional and legal-rational structures and thus corresponds to Weber’s notion of legitimacy in crisis. In “The Second Coming”, the haunting vision of a “rough beast” approaching Bethlehem implies the emergence of a new charismatic force that is unpredictable, radical, and potentially destructive. However, while charismatic authority can serve as a means of renewal, Yeats’s apocalyptic tone in the poem suggests scepticism about whether such figures restore order or merely accelerate disintegration. By portraying the transition from a crumbling system to an uncertain future, the poem raises a critical question: Does the collapse of legitimacy inherently invite the rise of tyranny rather than transformation? Combining Yeats’s apocalyptic vision with Weber’s socio-political concepts, this study explores how “The Second Coming” anticipates the conditions under which charismatic leaders rise in times of upheaval. It also considers Yeats’s own ambivalence towards this transformation and asks whether charismatic authority in the poem represents a necessary renewal or a descent into deeper disorder. The Weberian reading of “The Second Coming” emphasises the continuing importance of understanding the fragile and cyclical nature of political legitimacy in moments of unprecedented crisis.